The thalamic reuniens is associated with consolidation of non-spatial memory too - Hamilton, Jennifer J.; Dalrymple-Alford, John C. (Frontiers in Behavioral Neuroscience, 2023)
The nucleus reuniens (RE) is situated in the midline thalamus and provides a key link between hippocampus and prefrontal cortex. This anatomical relationship positions the Re as an ideal candidate to facilitate memory consolidation. Evidence is, however, lacking whether this role extends beyond spatial memory and contextual fear memory, both of which are strongly associated with hippocampal function. We therefore trained intact male Long-Evans rats on an odour-trace-object paired-association task in which the explicit 10-second delay between paired items renders the task sensitive to hippocampal function. Neurons in the RE showed markedly increased immediate early gene (Zif268) activation when rats were re-tested for the previous non-spatial memory 25 days after acquisition training, relative to a group tested at 5-days post-acquisition, as well as a control group tested 25 days after acquisition but with a new pair of non-spatial stimuli, and home cage controls. The remote recall group also showed relatively augmented IEG expression in the superficial layers of the medial PFC (anterior cingulate cortex and prelimbic cortex). These findings support the conclusion that the RE is preferentially engaged during remote recall in this non-spatial task and thus has a role beyond spatial memory and contextual fear memory.